Descriptive study: the novel "full spectrum people-with-opioid-use-disorder care model" - Richard Gadomski; Snehal Bhatt; Jessica Gross; Juan Antonio Dixon; Phillip Fiuty; Max Shapiro; Rafael Fernandez-Mancha; Julie Salvador (BMC, 2023)
Abstract Background People with Opioid Use Disorder (PWOUD) represent an underserved and marginalized population for whom treatment gaps exist. Low-barrier programs like mobile care units and street outreach programs have yielded increased access to buprenorphine and social services, however, OUD pertinent co-occurring behavioral health and medical conditions are frequently left unaddressed. A novel, tailored, comprehensive care delivery model may reduce disparities and improve access to care across a range of pathologies in this historically difficult to reach population and enhance efforts to provide universal treatment access in a harm reduction setting. Methods Descriptive data were collected and analyzed regarding patient demographics, retention in treatment and services rendered at a new, wrap-around, low-barrier buprenorphine clinic established at an existing harm reduction site in New Mexico between August 1, 2020, and August 31, 2021. Results 203 people used any service at the newly implemented program, 137 of whom specifically obtained medical and/or behavioral health care services including prescriptions for buprenorphine at least once from the physician onsite. Thirty-seven unique medical and psychiatric conditions were treated, representing a total of 565 separate encounters. The most common service utilized was buprenorphine treatment for opioid use disorder (81%), followed by treatment for post-traumatic stress disorder (62%), anxiety (44.5%) and depression (40.9%). Retention in buprenorphine treatment was 31.2% at 6 months. Conclusions An innovative, multidisciplinary, buprenorphine-centric care model, which targets a wide range of OUD pertinent pathologies while employing a harm reduction approach, can enhance utilization of these services among an underserved PWOUD population in a manner which moves our health system toward universal OUD treatment access thereby potentially reducing overdose and existing disparities.